Three-dimensional parametric study of stone column-supported embankments on soft soils - Daniela Marques (2018)
Parametric studies of an embankment on soft soils reinforced with stone columns are performed using a computer program based on the finite element method. The computer program incorporates the Biot consolidation theory (fully coupled formulation of the flow and equilibrium equations) with constitutive relations simulated by the p-q-theta critical state model. A 3D numerical approach is used to study the influence of the following parameters: construction time of the embankment; permeability anisotropy of the soft soil; deformability of the stone column. Special emphasis is given to comparisons, during and after the construction period, of the excess pore pressures, settlements, horizontal displacements, stress levels and stress concentration factor. The results indicate that the consolidation of soft soil is significantly influenced by the permeability anisotropy and construction time of the embankment. The deformability of the stone column expressively influences the long term settlements and horizontal displacements.